Effect of Oregano and Marjoram Essential Oils on the Physical and Antimicrobial Properties of Chitosan Based Systems. (20th June 2017) - Sedlaříková, Jana; Doležalová, Magda; Egner, Pavlína; Pavlačková, Jana; Krejčí, Jiří; Rudolf, Ondřej; Peer, Petra
Abstract : The effect of two essential oils (EOs), from Origanum vulgare and Origanum majorana, their structural properties, and concentration on physical and antimicrobial characteristics of chitosan based solutions as well as films was investigated. Results showed that significantly different behaviour was induced by variation in the compositions of given essential oils. Film-forming solutions (FFS) containing oregano oil comprised considerably greater particles in comparison with the marjoram samples. Similarly, structural changes were confirmed by SEM analysis of chitosan films modified with the EOs; the smaller particles of the marjoram oil demonstrated better compatibility with chitosan matrix. However, chitosan films enriched with the oregano oil showed significantly superior antimicrobial activity compared to the marjoram. The dissimilar effects of the two EOs were also observed by water vapour pressure (WVP) measurement; increasing the amount of oregano oil triggered a drop in the WVP of the prepared films, whereas the marjoram oil had a negligible impact in this respect. These results suggest that the structural features of active substances in the EOs play a crucial role in determining the final properties of FFS and biofilm systems.